Optimization of yeast (Saccharomyces cerevisiae) RNA isolation method for real-time quantitative PCR andmicroarray analysis - Yılmaz, Remziye; Akça, Oya; Baloğlu, Mehmet Cengiz; Öz, Mehmet Tufan; Öktem, Hüseyin Avni; Yücel, Meral (African Journal of Biotechnology Vol. 11(5), pp. 1046-1053, 16 January, 2012, 2012)
Quality of the starting RNA is indispensably important for obtaining highly reproducible quantitative polymerase chain reaction (qPCR) and microarray results for all organisms as well as S. cerevisiae. Isolating RNA from yeast cells with a maximum quality was especially critical since these cells were rich in polysaccharides and proteins. The method has been optimized through modification pretreatment applications for the isolation of S. cerevisiae RNA for qPCR and microarray analysis. Two extraction assay a TRIzol reagent-based method with three pretreatment applications and a commercially available kit with own pretreatment application, were compared for this purpose. Furthermore, the concentration yeast cells and enzyme were controlled in the range of 2 × 106 to 6 × 107 cells and 0.5 to 5 mg/ml, respectively to prevent RNA yields decrease and RNA degradation. Results of RNA isolation of the middle scales of yeast cells and enzyme concentrations which obtained fluxional deduct were not discussed here. Concentration and integrity of RNA samples were determined by μL spectrophotometer and Bioanalyzer, respectively. Quality of cDNA prepared from RNA samples was inspected with amplification using 18SrRNA primers in qPCR reactions. Furthermore, quality of RNA samples were evaluated using quality control parameters associated with performance of the assay and hybridization in microarray experiments. The highest yield and quality of RNA, which was appropriate for reverse transcription, cDNA library construction, qPCR reactions and microarray hybridizations without further processing was obtained by using Protocol C which used highest yeast cell and enzyme concentrations during the pretreatment application.
Keywords: RNA isolation, Saccharomyces cerevisiae, quantitative PCR, microarray.